ELEMENTAL ESTIMATION RISK IN NEW AND ALTERATION CONSTRUCTION PROJECTS - Bayley, Gillian Elizabeth (My University, 2011)
In the competitive construction industry where standard professional fees are deregulated, precontract planning work is executed at the professional’s risk. Cost estimators prepare project estimates with very little information thereby encumbering themselves with increasing financial risks. The principal concern is the possibility of a substantial variance between final construction cost and estimated cost, resulting in a claim against the estimator. The objective is to maximise the accuracy of the estimate by using a modest amount of information within a short period. In South Africa there are increasing numbers of alteration projects, which are believed to contain a higher financial risk profile than new developments. The purpose of this research was to explore at conceptual design phase, the risks of elemental costs in new and alteration residential projects. The data revealed that new residential developments contained greater financial variances at conceptual design stage than alteration work. The elemental cost distributions used in the model and the unexpected risk profiles were presented to experienced construction industry professionals for discussion and evaluation. The findings indicated that at the preliminary planning phase, alteration work did not attribute greater risks to the estimator if the estimate is underpinned by suitable qualifications. The research furthermore highlighted the need for greater investigation into risk profiles of all sectors of the construction industry.
MBA - WBS